Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
Gravition as Consciousness-Induced Information Pressure-a Foundational Mechanism for Mass Generation
Gravition as Consciousness-Induced Information Pressure-a Foundational Mechanism for Mass Generation